The integrated cultural landscape of North Gidley Island: Coastal, intertidal and nearshore archaeology in Murujuga (Dampier Archipelago), Western Australia. Issue 3 (2nd September 2021) - Leach, Jerem; Wiseman, Chelsea; O'Leary, Michael; McDonald, Jo; McCarthy, John; Morrison, Patrick; Jeffries, Peter; Hacker, Jorg; Ulm, Sean; Bailey, Geoff; Benjamin, Jonathan
Abstract: Recent studies conducted in Murujuga Sea Country have confirmed that Indigenous Australian archaeology does not end at the modern shore. Since the earliest peopling of the Australian continent, sea levels have fluctuated significantly, dropping as much as 130 m below modern mean sea-level during the Last Glacial Maximum (LGM). During this period, the continent (including Australia and New Guinea) represented a landmass one-third larger than present day Australia. As sea levels rose following the LGM, this extensive cultural landscape was inundated. The recent reporting of archaeological remains in a submerged context at Murujuga has enabled an integrated analysis of the archaeological landscape, based on direct evidence from archaeological sites that were originally formed on dry land, but are now located in intertidal and submerged environments. This study applies a landscape analysis centred on the submerged Cape Bruguieres channel site, and the Gidley Islands, where submerged, intertidal and coastal archaeology has been recorded. Aerial, pedestrian, and intertidal archaeological surveys were conducted to investigate the onshore and offshore landscape, providing new evidence with which to place the stone artefacts in the Cape Bruguieres channel into a wider context. Rock art engravings, grinding patches, quarries and upstanding stones – some of which are in the intertidal zone – point to the use of a landscape that is now submerged and to the possibility of discovering new underwater sites. By integrating evidence from subtidal and intertidal contexts with the onshore record, we explore the cultural landscape above and below the 'waterline' as a continuum.